2003
DOI: 10.1142/s0192415x03000898
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy Assessment of Chungpyesagan-tang for Acute Ischemic Stroke

Abstract: Chungpyesagan-tang is one of the most well-known traditional herbal formulations frequently used for treatment of acute stroke in Korea. Therefore, this study aims to assess the clinical safety and efficacy of chungpyesagan-tang on acute ischemic stroke. We recruited acute cerebral infarction subjects within 1 week after onset time. Then, we prescribed chungpyesagan-tang to an Oriental medical treatment group (OM-group) for 2 weeks and enrolled a Western medical treatment group (WM-group) which received only W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Usage of herbal prescriptions on acute ischemic stroke patients has been studied over the years [7–9], but no research was carried out to verify the necessity and usefulness of the pattern identification. Pattern identification is a meaningful diagnostic tool of TKM as it allows individualized treatment, maximizing its effectiveness and minimizing its adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usage of herbal prescriptions on acute ischemic stroke patients has been studied over the years [7–9], but no research was carried out to verify the necessity and usefulness of the pattern identification. Pattern identification is a meaningful diagnostic tool of TKM as it allows individualized treatment, maximizing its effectiveness and minimizing its adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the necessity and usefulness of pattern identification have not been verified yet. Many herbal prescriptions have been proven to have a beneficial effect in acute stroke patients [7–9], but the relation between the efficacy and the pattern identification was not indicated.…”
Section: Introductionmentioning
confidence: 99%
“…Other anti‐platelet drugs such as clopidogrel, ticlopidine, extended‐release dipyridamole and warfarin have potentially severe complications or are not readily available [3] . On the other hand, increasing preliminary studies in animal models have indicated that traditional Chinese medicines may be useful for treating or preventing AIS [4–8] . However, large, randomized clinical trials and further research into the action mechanisms are necessary to ensure the safety and efficacy of these Chinese medicines [8] …”
Section: Introductionmentioning
confidence: 99%
“…The traditional Chinese herb, Rhizoma ligustricus , has a long history as a treatment for cardiovascular and cerebrovascular diseases in Asia [5,9–11] . Tetramethylpyrazine (TMP), the active component of Rhizoma ligustricus , has been studied in several animal models of AIS with promising results; [12–15] but most Rhizoma ligusticus on the market are cultivars with extremely low concentrations of TMP which can also be easily lost by sublimation during the extraction procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Jung et al (2003) suggested in their alleged safety and efficacy assessment that Chungpyesagan-tang may have therapeutic effects in reducing the severity of ischemic stroke and improving functional recovery without the danger of a tendency to hemorrhage. We have concerns relating to this preparation, as tested, on the following grounds.…”
mentioning
confidence: 99%